Building The Next Generation Blast Experiment - Lourie, Nathan Patrick (2019)
Maps of the polarized thermal emission from dust in our galaxy hold the keys to unlock multiple astrophysical and cosmological questions. For measurements of the polarized cosmic microwave background (CMB), this dust emission is the dominant foreground. Subtracting this dust signal from the data is a critical step in the search for the weak primordial signatures of cosmic inflation. Mapping the magnetic field morphology of galactic dust can also shed light on the evolution of the giant molecular clouds which are the hotbeds of star formation in the galaxy. The Next Generation Balloon-Borne Large Aperture Submillimeter Telescope (BLAST-TNG) is a submillimeter mapping experiment which features three microwave kinetic inductance detector (MKID) arrays operating over 30% bandwidths centered at 250, 350, and 500 μm. These highly- multiplexed, high-sensitivity arrays, featuring 918, 469, and 272 dual-polarization pixels, are coupled to a 2.5 m diameter primary mirror and a cryogenic optical system providing diffraction-limited resolution of 30′′, 41′′, and 50′′ respectively. The arrays are cooled to ∼275 mK in a liquid-helium-cooled cryogenic receiver which will enable observations over the course of a 28-day stratospheric balloon flight from McMurdo Station in Antarctica as part of NASA’s long-duration-balloon program, planned for the 2018/2019 winter campaign. Doctor of Philosophy (PhD)